Written exposure therapy for PTSD a brief treatment approach for mental health professionals - Sloan, Denise M. ca. 20./21. Jh (American Psychological Association, 2025)
Now in a new edition, a comprehensive manual with clear, step-by-step instructions and practical examples for using written exposure therapy in clinical practice with trauma survivors with PTSD.